Magnetoteluric Modelling in High Noise of Low Frequency Signal - LAESANPURA, AGUS; Larasati, Nindia E.; Sugianto, Asep; Yunian, Wahyu Eko (Indonesian Journal of Physics, 2023)
Magnetoteluric(MT) modelling geophysics in high noise areas is a challenging task. One part is the precious data for subsurface reconstruction, the other, the noise will a priori annoy the outcome. Through simulation and an example fact in the field, these two phenomena will be discussed. The simulation will propose the ideal model without and with noise, running on the Bostick inversion. Noise varies several schemas in two types of curves. Occam and Bostick algorithms will be used to run the inversion scheme. The trade of the advantages and disadvantages is then compared to a prior model in the field where MT data and geologic cross section are available. Two scenarios are available, one is to use data with treatment using available schema, and the other is to use data by cutting off the noise contaminant segment, and finally to see the resulted through 2D modelling process. The resultant shows the model use the ideal signal without noise through inversion resulting is a better than the other with a noisy signal experiencing treatment, notably in level shallow part. The geologic cross section and gravity model is available to support these results.